Metal hydroxide nanofiber as well as preparation method and application thereof
By electrochemically activating bimetallic CoxNiy-MOF nanofibers, metal hydroxide nanofibers with high OER activity, durability and electrochemical stability were prepared, which solved the problems of slow kinetics and poor durability of existing electrocatalysts in OER, and achieved efficient and low-cost electrolysis of hydrogen production.
Patent Information
- Application Number
- CN202411861502.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
AI Technical Summary
The existing electrocatalysts have slow kinetics and low selectivity in the oxygen precipitation reaction (OER), resulting in low efficiency and high cost of hydrogen production in electrolytic water, and poor durability and electrochemical stability of MOF-based catalysts.
By electrochemically activating bimetallic CoxNiy-MOF nanofibers, metal hydroxide nanofibers with high OER catalytic activity, durability and electrochemical stability were prepared. The nanofiber has a hollow tubular or core-shell-covered structure, the outer shell consists of cobalt-nickel hydroxide and the inner core is CoxNiy-MOF.
It achieves high OER activity, excellent durability and electrochemical stability, and has a simple preparation method, controllable process and low cost, which is suitable for large-scale industrial applications.
Smart Images

Figure CN119663354A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalysis, and in particular to a metal hydroxide nanofiber and a preparation method and application thereof. Background Art
[0002] With the continuous rise of aerospace, renewable energy, electric vehicles and smart electronic equipment, as well as the increasing energy shortage and environmental crisis, the development of clean, efficient and sustainable new energy has become increasingly important, and efficient energy conversion and storage systems have also become a hot topic of concern. Hydrogen production by water electrolysis is an important way to achieve green and clean energy production using renewable energy, which is of great significance for alleviating energy shortage and environmental crisis. However, the kinetics of electrocatalytic reactions are slow and the selectivity is low, resulting in low efficiency and high cost of hydrogen production by water electrolysis. Therefore, the development of high-performance, low-cost electrocatalysts, especially oxygen evolution reaction (OER) catalysts at the anode, is the key to improving the efficiency of hydrogen production by water electrolysis.
[0003] Metal-organic framework (MOF) materials have dispersed metal active sites, adjustable coordination environment and rich porous structure, which have attracted wide attention in the field of electrocatalysis. Studies have shown that metal atoms in transition metal (Fe, Co, Ni, etc.)-based MOF catalysts can be oxidized to form higher valence metal sites (hydroxides and oxyhydroxides) under OER conditions, and these high valence sites help to reduce the kinetic energy barrier in the OER process, thereby increasing the catalytic reaction rate (ZHOU J, et al. Interpretable Data-Driven Descriptors for Establishing the Structure-Activity Relationship of Metal-Organic Frameworks Toward Oxygen Evolution Reaction [J]. Angew Chem Int Edit, 2024). However, MOF-based catalysts are pre-catalysts and usually exist as precursors in catalytic reactions. When MOF-based catalysts are used for oxygen evolution reactions, drastic surface reconstruction will occur on the catalyst surface. Although the initial OER performance of the formed MOF-derived intermediates is better than that of traditional metal hydroxide catalysts, the durability and electrochemical stability of the catalyst are poor (MAXX, et al. Tuning the Reconstruction of Metal-Organic Frameworks during the Oxygen Evolution Reaction[J]. Acs Catal, 2024), which makes it difficult to fully meet the requirements of practical applications.
[0004] Therefore, it is of great significance to develop an OER catalyst with high OER activity, excellent durability and electrochemical stability, simple preparation method and low cost. Summary of the invention
[0005] The purpose of the present invention is to provide a metal hydroxide nanofiber and a preparation method and application thereof.
[0006] The technical solution adopted by the present invention is:
[0007] A metal hydroxide nanofiber, comprising cobalt-nickel hydroxide, x Ni y -MOF nanofibers are made by electrochemical activation, <x<1,x+y=1。
[0008] Preferably, a metal hydroxide nanofiber, comprising cobalt-nickel hydroxide, x Ni y -MOF nanofibers are made by electrochemical activation, 0.25≤x≤0.75, x+y=1.
[0009] Preferably, the metal hydroxide nanofibers are in a hollow tubular structure, composed of cobalt-nickel hydroxide, with a length of 0.5 μm to 5 μm, an outer diameter of 100 nm to 300 nm, and an inner diameter of 50 nm to 150 nm.
[0010] Preferably, the metal hydroxide nanofiber has a core-shell coating structure, a length of 1 μm to 10 μm, an outer diameter of 50 nm to 350 nm, and an inner core composed of Co x Ni y -MOF, the diameter of the inner core is 25nm to 200nm, and the composition of the outer shell includes cobalt-nickel hydroxide.
[0011] Preferably, the metal hydroxide nanofiber has a core-shell coating structure, a length of 1 μm to 13 μm, an outer diameter of 50 nm to 150 nm, and an inner core composition including Co x Ni y -MOF, the diameter of the inner core is 45nm to 130nm, and the composition of the outer shell includes cobalt-nickel hydroxide.
[0012] A method for preparing the metal hydroxide nanofibers as described above comprises the following steps:
[0013] 1) Add cobalt salt, nickel salt and 2,5-dihydroxyterephthalic acid into methanol for reaction, then add the obtained solid product into water for hydrothermal recrystallization to obtain Co x Ni y-MOF nanofibers;
[0014] 2) Co x Ni y -MOF nanofibers are electrochemically activated to achieve structural reformation, thereby obtaining metal hydroxide nanofibers.
[0015] Preferably, in step 1), the ratio of the total molar amount of the cobalt salt and the nickel salt to the molar amount of 2,5-dihydroxyterephthalic acid is 1:0.9-1.1.
[0016] Preferably, the cobalt salt in step 1) is at least one of cobalt nitrate, cobalt sulfate, cobalt carbonate, cobalt acetate and cobalt acetylacetonate.
[0017] Preferably, the nickel salt in step 1) is at least one of nickel nitrate, nickel sulfate, nickel carbonate, nickel acetate and nickel acetylacetonate.
[0018] Preferably, the reaction in step 1) is carried out at a temperature of 20°C to 40°C, and the reaction time is 20min to 120min.
[0019] Preferably, the hydrothermal recrystallization in step 1) is carried out at a temperature of 125° C. to 175° C., and the reaction time is 12 h to 24 h.
[0020] Preferably, the electrochemical activation in step 2) comprises the following operations: x Ni y -MOF nanofibers were loaded on a carbon electrode to make a working electrode, and then cyclic voltammetry scanning was performed with a Hg / HgO electrode as a reference electrode, a platinum electrode as a counter electrode, and a KOH solution as an electrolyte. The scanning rate was 1 mV / s to 100 mV / s, the scanning potential range was 0.925 V to 1.525 V, and the number of scanning circles was 5 to 200 circles.
[0021] Preferably, the load comprises the following operations: x Ni y -MOF nanofibers were ultrasonically dispersed in ethanol to prepare a dispersion, which was then coated on a carbon electrode and dried.
[0022] Preferably, the carbon electrode is one of carbon paper and carbon cloth.
[0023] Preferably, the drying is carried out at a temperature of 60° C. to 75° C., and the drying time is 10 min to 30 min.
[0024] Preferably, the Co x Ni y -The loading amount of MOF nanofibers on the carbon electrode is 0.16 mg / cm 2 ~0.80mg / cm2 .
[0025] Preferably, the electrochemical activation in step 2) is carried out at a temperature of 20°C to 40°C.
[0026] An oxygen evolution reaction catalyst comprises the metal hydroxide nanofiber.
[0027] An application of the metal hydroxide nanofiber as described above in producing hydrogen by electrolysis of water.
[0028] The beneficial effects of the present invention are as follows: the metal hydroxide nanofibers of the present invention, when used as OER catalysts, have the advantages of high OER activity, excellent durability and electrochemical stability, and the preparation method thereof is simple, the process is controllable, and the cost is low, and the nanofibers are suitable for large-scale industrial applications in the field of hydrogen production by electrolysis of water.
[0029] Specifically:
[0030] 1) The present invention uses an electrochemical method to treat the bimetallic Co x Ni y -MOF materials undergo surface reformation, and the resulting metal hydroxide nanofibers have high OER catalytic activity;
[0031] 2) The present invention is to treat the bimetallic Co x Ni y -The bimetallic ratio of MOF materials can be adjusted to obtain metal hydroxide nanofibers with different structures (hollow tubular nanofibers and core-shell structured nanofibers). Since the corrosion resistance of Ni sites is stronger than that of Co sites, the introduction of Ni gives metal hydroxide nanofibers excellent durability and electrochemical stability.
[0032] 3) The preparation method of the metal hydroxide nanofibers of the present invention is simple, the process is controllable, and the cost is low, and it is suitable for large-scale industrial production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is Co in Example 1 0.75 Ni 0.25 -SEM image of MOF nanofibers.
[0034] Figure 2 This is the SEM image of the metal hydroxide nanofibers in Example 1.
[0035] Figure 3 is Co in Example 1 0.75 Ni 0.25 -MOF nanofibers, Co in Example 2 0.5 Ni 0.5 -MOF nanofibers, Co in Example 30.25 Ni 0.75 -MOF nanofibers, Co in Comparative Example 1 1 Ni 0 -MOF nanofibers and Co in Comparative Example 2 0 Ni 1 -XRD pattern of MOF nanofibers.
[0036] Figure 4 is Co in Example 1 0.75 Ni 0.25 -MOF nanofibers, Co in Example 2 0.5 Ni 0.5 -MOF nanofibers, Co in Example 3 0.25 Ni 0.75 -MOF nanofibers, Co in Comparative Example 1 1 Ni 0 -MOF nanofibers and Co in Comparative Example 2 0 Ni 1 -FT-IR image of MOF nanofibers.
[0037] Figure 5 1 and 2 are LSV curves of the metal hydroxide nanofibers in Examples 1 to 3 and Comparative Examples 1 to 2.
[0038] Figure 6 It is a graph showing the Tafel slope test results of the metal hydroxide nanofibers in Examples 1 to 3 and Comparative Examples 1 to 2.
[0039] Figure 7 is Co in Example 2 0.5 Ni 0.5 -SEM image of MOF nanofibers.
[0040] Figure 8 This is the SEM image of the metal hydroxide nanofibers in Example 2.
[0041] Fig. 9 is Co in Example 3 0.25 Ni 0.75 -SEM image of MOF nanofibers.
[0042] Fig.10 This is the SEM image of the metal hydroxide nanofibers in Example 3.
[0043] Fig.11 is Co in Comparative Example 1 1 Ni 0 -SEM image of MOF nanofibers.
[0044] Fig.12This is the SEM image of the metal hydroxide nanofibers in Comparative Example 1.
[0045] Fig.13 is Co in Comparative Example 2 0 Ni 1 -SEM image of MOF nanofibers.
[0046] Fig.14 This is the SEM image of the metal hydroxide nanofibers in Comparative Example 2. DETAILED DESCRIPTION
[0047] The present invention will be further explained and illustrated below in conjunction with specific embodiments.
[0048] Embodiment 1:
[0049] A metal hydroxide nanofiber, the preparation method of which is as follows:
[0050] 1) 3.0 mmol of Co(C 2 H 3 O 2 ) 2 ·4H 2 O, 1.0mmol Ni(C 2 H 3 O 2 ) 2 ·4H 2 O and 4.0 mmol of 2,5-dihydroxyterephthalic acid (H 4 dobdc) were stirred and dissolved in 45 mL, 45 mL and 60 mL of anhydrous methanol to prepare Co(C 2 H 3 O 2 ) 2 Solution, Ni(C 2 H 3 O 2 ) 2 solution and 2,5-dihydroxyterephthalic acid solution, and then Ni(C 2 H 3 O 2 ) 2 Add dropwise to Co(C 2 H 3 O 2 ) 2The solution was added and stirred at room temperature for 15 minutes. The mixed solution was then added dropwise to the 2,5-dihydroxyterephthalic acid solution. After the addition, it was vigorously stirred at room temperature for 2 hours. The precipitate obtained by the reaction was washed with distilled water and separated by a centrifuge. The solid obtained by centrifugation was dispersed in 30 mL of distilled water and transferred to a PTFE-lined hydrothermal autoclave reactor. The reaction was carried out at 125°C for 12 hours. The precipitate obtained by the reaction was washed with distilled water and separated by a centrifuge. The solid obtained by centrifugation was placed at -80°C for freeze-drying to obtain Co 0.75 Ni 0.25 -MOF nanofibers;
[0051] 2) 1 mg of Co 0.75 Ni 0.25 -MOF nanofibers were added to 1 mL of anhydrous ethanol and ultrasonically treated for 10 min. The resulting dispersion was then coated on carbon paper (CP) and dried on a heating platform at 65 °C for 10 min to prepare a working electrode (WE; electrode area 6.25 cm 2 ,Co 0.75 Ni 0.25 -The loading amount of MOF nanofibers is 0.16 mg / cm 2 ), and then use Hg / HgO electrode as reference electrode (RE), platinum mesh as counter electrode (CE), and 1.0 mol / L KOH solution as electrolyte to perform cyclic voltammetry scanning with a scanning rate of 10 mV / s, a scanning potential range of 0.925 V to 1.525 V, and 30 scanning circles to obtain metal hydroxide nanofibers.
[0052] Performance Test:
[0053] a) Co in this embodiment 0.75 Ni 0.25 -Scanning electron microscope (SEM) image of MOF nanofibers Figure 1 As shown, the SEM image of the metal hydroxide nanofibers in this embodiment is as follows Figure 2 As shown, Co in this embodiment 0.75 Ni 0.25 -X-ray diffraction (XRD) pattern of MOF nanofibers Figure 3 As shown, the Fourier transform infrared spectrum (FT-IR) of the metal hydroxide nanofibers in this embodiment is as follows Figure 4 shown.
[0054] Depend on Figure 1 and Figure 3 It can be seen that Co 0.75 Ni 0.25-MOF nanofibers have a length of 5 μm to 20 μm and a diameter of 100 nm to 350 nm, wherein the atomic percentages of Co and Ni are 22.20% and 6.69%, respectively (Table 1), and the atomic ratio within the fiber is substantially consistent with the set feed ratio.
[0055] Depend on Figure 2 and Figure 4 It can be seen that Co 0.75 Ni 0.25 The metal hydroxide nanofibers obtained by electrochemically activating the MOF nanofibers to achieve structural reformation have a hollow tubular structure composed of cobalt-nickel hydroxide, a length of 0.5 μm to 5 μm, an outer diameter of 100 nm to 300 nm, and an inner diameter of 50 nm to 150 nm.
[0056] b) The metal hydroxide nanofibers (supported on carbon paper) in this example were used as working electrodes, and a three-electrode system was assembled with Hg / HgO electrode as reference electrode, platinum mesh as counter electrode, and 1.0 mol / L KOH solution as electrolyte to perform linear voltammetry (LSV) scanning to test the OER performance of the metal hydroxide nanofibers. The scanning rate was 10 mV / s, and the scanning potential range was 1.0 V to 1.8 V. The obtained LSV curve is shown in FIG. Figure 5 As shown, the Tafel slope test results are as follows Figure 6 shown.
[0057] Depend on Figure 5 and Figure 6 It can be seen that the metal hydroxide nanofibers in this embodiment have a current density of 20 mA / cm 2 When , the overpotential is 430.1 mV, which is lower than that of the metal hydroxide nanomaterials derived from single metal MOFs (Comparative Example 1 is 500.4 mV, and Comparative Example 2 is 590.5 mV); the Tafel slope of the metal hydroxide nanofibers in this embodiment is 83.7 mV / dec, which is lower than that of the metal hydroxide nanomaterials derived from single metal MOFs (Comparative Example 1 is 88.1 mV / dec, and Comparative Example 2 is 167.6 mV / dec); In summary, the metal hydroxide nanofibers in this embodiment have better OER performance than those in Comparative Examples 1 and 2.
[0058] Embodiment 2:
[0059] A metal hydroxide nanofiber, the preparation method of which is as follows:
[0060] 1) 2.0 mmol of Co(C 2 H 3 O 2 ) 2 ·4H 2O, 2.0 mmol Ni(C 2 H 3 O 2 ) 2 ·4H 2 O and 4.0 mmol of 2,5-dihydroxyterephthalic acid (H 4 dobdc) were stirred and dissolved in 45 mL, 45 mL and 60 mL of anhydrous methanol to prepare Co(C 2 H 3 O 2 ) 2 Solution, Ni(C 2 H 3 O 2 ) 2 solution and 2,5-dihydroxyterephthalic acid solution, and then Ni(C 2 H 3 O 2 ) 2 Add dropwise to Co(C 2 H 3 O 2 ) 2 The solution was added and stirred at room temperature for 15 minutes. The mixed solution was then added dropwise to the 2,5-dihydroxyterephthalic acid solution. After the addition, it was vigorously stirred at room temperature for 2 hours. The precipitate obtained by the reaction was washed with distilled water and separated by a centrifuge. The solid obtained by centrifugation was dispersed in 30 mL of distilled water and transferred to a PTFE-lined hydrothermal autoclave reactor. The reaction was carried out at 125°C for 12 hours. The precipitate obtained by the reaction was washed with distilled water and separated by a centrifuge. The solid obtained by centrifugation was placed at -80°C for freeze-drying to obtain Co 0.5 Ni 0.5 -MOF nanofibers;
[0061] 2) 1 mg of Co 0.5 Ni 0.5 -MOF nanofibers were added to 1 mL of anhydrous ethanol and ultrasonically treated for 10 min. The resulting dispersion was then coated on carbon paper and dried on a heating platform at 65 °C for 10 min to prepare a working electrode (electrode area 6.25 cm 2 ,Co 0.5 Ni 0.5 -The loading amount of MOF nanofibers is 0.16 mg / cm 2 ), and then use Hg / HgO electrode as reference electrode, platinum mesh as counter electrode, 1.0 mol / L KOH solution as electrolyte to perform cyclic voltammetry scanning, the scanning rate is 10 mV / s, the scanning potential range is 0.925 V ~ 1.525 V, the scanning number of circles is 30 circles, and metal hydroxide nanofibers are obtained.
[0062] Performance Test:
[0063] a) Co in this embodiment 0.5 Ni 0.5 -SEM images of MOF nanofibers Figure 7 As shown, the SEM image of the metal hydroxide nanofibers in this embodiment is as follows Figure 8 As shown, Co in this embodiment 0.5 Ni 0.5 -XRD pattern of MOF nanofibers Figure 3 As shown, the FT-IR image of the metal hydroxide nanofibers in this embodiment is as follows Figure 4 shown.
[0064] Depend on Figure 7 and Figure 3 It can be seen that Co 0.5 Ni 0.5 -MOF nanofibers have a length of 2 μm to 20 μm and a diameter of 100 nm to 300 nm, wherein the atomic percentages of Co and Ni are 13.40% and 12.80%, respectively (Table 1), and the atomic ratio within the fiber is substantially consistent with the set feed ratio.
[0065] Depend on Figure 8 and Figure 4 It can be seen that Co 0.5 Ni 0.5 -MOF nanofibers are electrochemically activated to achieve structural reorganization. The metal hydroxide nanofibers have a core-shell coating structure, a length of 1 μm to 10 μm, an outer diameter of 50 nm to 350 nm, and an inner core composed of Co 0.5 Ni 0.5 -MOF, the diameter of the inner core is 25nm~200nm, and the outer shell is composed of cobalt-nickel hydroxide.
[0066] b) The metal hydroxide nanofibers (supported on carbon paper) in this example were used as working electrodes, and a three-electrode system was assembled with Hg / HgO electrode as reference electrode, platinum mesh as counter electrode, and 1.0 mol / L KOH solution as electrolyte to perform linear voltammetry (LSV) scanning to test the OER performance of the metal hydroxide nanofibers. The scanning rate was 10 mV / s, and the scanning potential range was 1.0 V to 1.8 V. The obtained LSV curve is shown in FIG. Figure 5 As shown, the Tafel slope test results are as follows Figure 6 shown.
[0067] Depend on Figure 5 and Figure 6 It can be seen that the metal hydroxide nanofibers in this embodiment have a current density of 20 mA / cm 2When , the overpotential is 506.9 mV, which is lower than that of the metal hydroxide nanomaterials derived from Ni-MOFs (590.5 mV in Comparative Example 2); the Tafel slope of the metal hydroxide nanofibers in this embodiment is 156.7 mV / dec, which is lower than that of the metal hydroxide nanomaterials derived from Ni-MOFs (167.6 mV / dec in Comparative Example 2); in summary, the metal hydroxide nanofibers in this embodiment have better OER performance than those in Comparative Example 2.
[0068] Embodiment 3:
[0069] A metal hydroxide nanofiber, the preparation method of which is as follows:
[0070] 1) 1.0 mmol of Co(C 2 H 3 O 2 ) 2 ·4H 2 O, 3.0mmol Ni(C 2 H 3 O 2 ) 2 ·4H 2 O and 4.0 mmol of 2,5-dihydroxyterephthalic acid (H 4 dobdc) were stirred and dissolved in 45 mL, 45 mL and 60 mL of anhydrous methanol to prepare Co(C 2 H 3 O 2 ) 2 Solution, Ni(C 2 H 3 O 2 ) 2 solution and 2,5-dihydroxyterephthalic acid solution, and then Ni(C 2 H 3 O 2 ) 2 Add dropwise to Co(C 2 H 3 O 2 ) 2 The solution was added and stirred at room temperature for 15 minutes. The mixed solution was then added dropwise to the 2,5-dihydroxyterephthalic acid solution. After the addition, it was vigorously stirred at room temperature for 2 hours. The precipitate obtained by the reaction was washed with distilled water and separated by a centrifuge. The solid obtained by centrifugation was dispersed in 30 mL of distilled water and transferred to a PTFE-lined hydrothermal autoclave reactor. The reaction was carried out at 125°C for 12 hours. The precipitate obtained by the reaction was washed with distilled water and separated by a centrifuge. The solid obtained by centrifugation was placed at -80°C for freeze-drying to obtain Co 0.25 Ni0.75 -MOF nanofibers;
[0071] 2) 1 mg of Co 0.25 Ni 0.75 -MOF nanofibers were added to 1 mL of anhydrous ethanol and ultrasonically treated for 10 min. The resulting dispersion was then coated on carbon paper and dried on a heating platform at 65 °C for 10 min to prepare a working electrode (electrode area 6.25 cm 2 ,Co 0.25 Ni 0.75 -The loading amount of MOF nanofibers is 0.16 mg / cm 2 ), and then use Hg / HgO electrode as reference electrode, platinum mesh as counter electrode, 1.0 mol / L KOH solution as electrolyte to perform cyclic voltammetry scanning, the scanning rate is 10 mV / s, the scanning potential range is 0.925 V ~ 1.525 V, the scanning number of circles is 30 circles, and metal hydroxide nanofibers are obtained.
[0072] Performance Test:
[0073] a) Co in this embodiment 0.25 Ni 0.75 -SEM images of MOF nanofibers Fig. 9 As shown, the SEM image of the metal hydroxide nanofibers in this embodiment is as follows Fig.10 As shown, Co in this embodiment 0.25 Ni 0.75 -XRD pattern of MOF nanofibers Figure 3 As shown, the FT-IR image of the metal hydroxide nanofibers in this embodiment is as follows Figure 4 shown.
[0074] Depend on Fig. 9 and Figure 3 It can be seen that Co 0.25 Ni 0.75 -MOF nanofibers have a length of 1 μm to 13 μm and a diameter of 50 nm to 350 nm, wherein the atomic percentages of Co and Ni are 8.10% and 18.10%, respectively (Table 1), and the atomic ratio within the fiber is substantially consistent with the set feed ratio.
[0075] Depend on Fig.10 and Figure 4 It can be seen that Co 0.25 Ni 0.75 -MOF nanofibers are electrochemically activated to achieve structural reorganization. The metal hydroxide nanofibers have a core-shell coating structure, a length of 1 μm to 13 μm, an outer diameter of 50 nm to 150 nm, and an inner core composed of Co 0.25 Ni 0.75-MOF, the diameter of the inner core is 45nm~130nm, and the outer shell is composed of cobalt-nickel hydroxide.
[0076] b) The metal hydroxide nanofibers (supported on carbon paper) in this example were used as working electrodes, and a three-electrode system was assembled with Hg / HgO electrode as reference electrode, platinum mesh as counter electrode, and 1.0 mol / L KOH solution as electrolyte to perform linear voltammetry (LSV) scanning to test the OER performance of the metal hydroxide nanofibers. The scanning rate was 10 mV / s, and the scanning potential range was 1.0 V to 1.8 V. The obtained LSV curve is shown in FIG. Figure 5 As shown, the Tafel slope test results are as follows Figure 6 shown.
[0077] Depend on Figure 5 and Figure 6 It can be seen that the metal hydroxide nanofibers in this embodiment have a current density of 20 mA / cm 2 When , the overpotential is 517.0 mV, which is lower than that of the metal hydroxide nanomaterials derived from Ni-MOFs (590.5 mV in Comparative Example 2); the Tafel slope of the metal hydroxide nanofibers in this embodiment is 133.3 mV / dec, which is lower than that of the metal hydroxide nanomaterials derived from Ni-MOFs (167.6 mV / dec in Comparative Example 2); in summary, the metal hydroxide nanofibers in this embodiment have better OER performance than those in Comparative Example 2.
[0078] Comparative Example 1:
[0079] A metal hydroxide nanofiber, the preparation method of which is as follows:
[0080] 1) 4.0 mmol of Co(C 2 H 3 O 2 ) 2 ·4H 2 O and 4.0 mmol of 2,5-dihydroxyterephthalic acid (H 4 dobdc) were stirred and dissolved in 90 mL and 60 mL of anhydrous methanol to prepare Co(C 2 H 3 O 2 ) 2 solution and 2,5-dihydroxyterephthalic acid solution, and then Co(C 2 H 3 O 2 ) 2The solution was added dropwise to the 2,5-dihydroxyterephthalic acid solution, and after the addition, it was vigorously stirred at room temperature for 2 hours, and then the precipitate obtained by the reaction was washed with distilled water and separated by a centrifuge. The solid obtained by centrifugation was dispersed in 30 mL of distilled water and then transferred to a PTFE-lined hydrothermal autoclave reactor, reacted at 125°C for 12 hours, and then the precipitate obtained by the reaction was washed with distilled water and separated by a centrifuge. The solid obtained by centrifugation was placed at -80°C for freeze-drying to obtain Co 1 Ni 0 -MOF nanofibers;
[0081] 2) 1 mg of Co 1 Ni 0 -MOF nanofibers were added to 1 mL of anhydrous ethanol and ultrasonically treated for 10 min. The resulting dispersion was then coated on carbon paper and dried on a heating platform at 65 °C for 10 min to prepare a working electrode (electrode area 6.25 cm 2 ,Co 1 Ni 0 -The loading amount of MOF nanofibers is 0.16 mg / cm 2 ), and then use Hg / HgO electrode as reference electrode, platinum mesh as counter electrode, 1.0 mol / L KOH solution as electrolyte to perform cyclic voltammetry scanning, the scanning rate is 10 mV / s, the scanning potential range is 0.925 V ~ 1.525 V, the scanning number of circles is 30 circles, and metal hydroxide nanofibers are obtained.
[0082] Performance Test:
[0083] a) Co in this comparative example 1 Ni 0 -SEM images of MOF nanofibers Fig.11 As shown, the SEM image of the metal hydroxide nanofibers in this comparative example is as follows Fig.12 As shown, Co in this comparative example 1 Ni 0 -XRD pattern of MOF nanofibers Figure 3 As shown, the FT-IR image of the metal hydroxide nanofibers in this comparative example is as follows Figure 4 shown.
[0084] Depend on Fig.11 and Figure 3 It can be seen that Co 1 Ni 0 -MOF nanofibers have a length of 10 μm to 120 μm, a diameter of 100 nm to 200 nm, and an atomic percentage of Co of 29.60% (Table 1).
[0085] Depend on Fig.12 and Figure 4 It can be seen that Co 1 Ni 0 -MOF nanofibers were electrochemically activated to achieve structural reorganization, and the MOF structure of the fibers collapsed to form flaky hydroxides.
[0086] b) The metal hydroxide nanofibers (supported on carbon paper) in this comparative example were used as working electrodes, and a three-electrode system was assembled with Hg / HgO electrode as reference electrode, platinum mesh as counter electrode, and 1.0 mol / L KOH solution as electrolyte to perform linear voltammetry (LSV) scanning to test the OER performance of the metal hydroxide nanofibers. The scanning rate was 10 mV / s, and the scanning potential range was 1.0 V to 1.8 V. The obtained LSV curve is shown in FIG. Figure 5 As shown, the Tafel slope test results are as follows Figure 6 shown.
[0087] Depend on Figure 5 and Figure 6 It can be seen that the metal hydroxide nanofibers in this comparative example have a current density of 20 mA / cm 2 When , the overpotential is 500.4 mV and the Tafel slope is 88.1 mV / dec, which has significantly worse OER performance than the metal hydroxide nanofibers in Example 1.
[0088] Comparative Example 2:
[0089] A metal hydroxide nanofiber, the preparation method of which is as follows:
[0090] 1) 4.0 mmol of Ni(C 2 H 3 O 2 ) 2 ·4H 2 O and 4.0 mmol of 2,5-dihydroxyterephthalic acid (H 4 dobdc) were stirred and dissolved in 90 mL and 60 mL of anhydrous methanol to prepare Ni(C 2 H 3 O 2 ) 2 solution and 2,5-dihydroxyterephthalic acid solution, and then Ni(C 2 H 3 O 2 ) 2The solution was added dropwise to the 2,5-dihydroxyterephthalic acid solution, and after the addition, it was vigorously stirred at room temperature for 2 hours, and then the precipitate obtained by the reaction was washed with distilled water and separated by a centrifuge. The solid obtained by centrifugation was dispersed in 30 mL of distilled water and then transferred to a PTFE-lined hydrothermal autoclave reactor, reacted at 125°C for 12 hours, and then the precipitate obtained by the reaction was washed with distilled water and separated by a centrifuge. The solid obtained by centrifugation was placed at -80°C for freeze-drying to obtain Co 0 Ni 1 -MOF nanofibers;
[0091] 2) 1 mg of Co 0 Ni 1 -MOF nanofibers were added to 1 mL of anhydrous ethanol and ultrasonically treated for 10 min. The resulting dispersion was then coated on carbon paper and dried on a heating platform at 65 °C for 10 min to prepare a working electrode (electrode area 6.25 cm 2 ,Co 0 Ni 1 -The loading amount of MOF nanofibers is 0.16 mg / cm 2 ), and then use Hg / HgO electrode as reference electrode, platinum mesh as counter electrode, 1.0 mol / L KOH solution as electrolyte to perform cyclic voltammetry scanning, the scanning rate is 10 mV / s, the scanning potential range is 0.925 V ~ 1.525 V, the scanning number of circles is 30 circles, and metal hydroxide nanofibers are obtained.
[0092] Performance Test:
[0093] a) Co in this comparative example 0 Ni 1 -SEM images of MOF nanofibers Fig.13 As shown, the SEM image of the metal hydroxide nanofibers in this comparative example is as follows Fig.14 As shown, Co in this comparative example 0 Ni 1 -XRD pattern of MOF nanofibers Figure 3 As shown, the FT-IR image of the metal hydroxide nanofibers in this comparative example is as follows Figure 4 shown.
[0094] Depend on Fig.13 and Figure 3 It can be seen that Co 0 Ni 1 -MOF nanofibers have a length of 1 μm to 5 μm, a diameter of 50 nm to 250 nm, and an atomic percentage of Ni of 27.20% (Table 1).
[0095] Depend on Fig.14 and Figure 4It can be seen that Co 0 Ni 1 -The metal hydroxide nanofibers obtained by electrochemical activation to achieve structural reformation of MOF nanofibers have a tubular structure with a wrinkled surface, a length of 1 μm to 5 μm, and a diameter of 50 nm to 250 nm.
[0096] b) The metal hydroxide nanofibers (supported on carbon paper) in this comparative example were used as working electrodes, and a three-electrode system was assembled with Hg / HgO electrode as reference electrode, platinum mesh as counter electrode, and 1.0 mol / L KOH solution as electrolyte to perform linear voltammetry (LSV) scanning to test the OER performance of the metal hydroxide nanofibers. The scanning rate was 10 mV / s, and the scanning potential range was 1.0 V to 1.8 V. The obtained LSV curve is shown in FIG. Figure 5 As shown, the Tafel slope test results are as follows Figure 6 shown.
[0097] Depend on Figure 5 and Figure 6 It can be seen that the metal hydroxide nanofibers in this comparative example have a current density of 20 mA / cm 2 When the overpotential is 590.5 mV, the Tafel slope is 167.6 mV / dec. It can be seen that the activity of metal hydroxides derived from Co-MOF-74 is better than that of metal hydroxides derived from Ni-MOF-74. The Co / Ni metal ratio in the MOFs precursor has a great influence on the OER activity of the material. 0.75 Ni 0.25 -MOF-74 derived metal hydroxide nanofibers showed the highest OER activity.
[0098] Note:
[0099] Co in Examples 1 to 3 and Comparative Examples 1 to 2 x Ni y -The inductively coupled plasma optical emission spectroscopy (ICP-OES) test results of MOF nanofibers are shown in the following table:
[0100] Table 1Co x Ni y -ICP-OES test results of MOF nanofibers
[0101]
[0102]
[0103] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A metal hydroxide nanofiber, characterized in that: The composition includes cobalt-nickel hydroxide; the metal hydroxide nanofibers are composed of Co x Ni y -MOF nanofibers are made by electrochemical activation, <x<1,x+y=1。 2. The metal hydroxide nanofiber according to claim 1, characterized in that: The metal hydroxide nanofiber is in a hollow tubular structure, and is composed of cobalt-nickel hydroxide, with a length of 0.5 μm to 5 μm, an outer diameter of 100 nm to 300 nm, and an inner diameter of 50 nm to 150 nm.
3. The metal hydroxide nanofiber according to claim 1, characterized in that: The metal hydroxide nanofiber has a core-shell coating structure, a length of 1 μm to 10 μm, an outer diameter of 50 nm to 350 nm, and an inner core comprising Co x Ni y -MOF, the diameter of the inner core is 25nm to 200nm, and the composition of the outer shell includes cobalt-nickel hydroxide.
4. The metal hydroxide nanofiber according to claim 1, characterized in that: The metal hydroxide nanofiber has a core-shell coating structure, a length of 1 μm to 13 μm, an outer diameter of 50 nm to 150 nm, and an inner core comprising Co x Ni y -MOF, the diameter of the inner core is 45nm to 130nm, and the composition of the outer shell includes cobalt-nickel hydroxide.
5. A method for preparing metal hydroxide nanofibers according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) Add cobalt salt, nickel salt and 2,5-dihydroxyterephthalic acid into methanol for reaction, then add the obtained solid product into water for hydrothermal recrystallization to obtain Co x Ni y -MOF nanofibers; 2) Co x Ni y -MOF nanofibers are electrochemically activated to achieve structural reformation, thereby obtaining metal hydroxide nanofibers.
6. The preparation method according to claim 5, characterized in that: The ratio of the total molar amount of the cobalt salt and the nickel salt in step 1) to the molar amount of 2,5-dihydroxyterephthalic acid is 1:0.9-1.1; the cobalt salt in step 1) is at least one of cobalt nitrate, cobalt sulfate, cobalt carbonate, cobalt acetate, and cobalt acetylacetonate; the nickel salt in step 1) is at least one of nickel nitrate, nickel sulfate, nickel carbonate, nickel acetate, and nickel acetylacetonate.
7. The preparation method according to claim 5 or 6, characterized in that: The reaction in step 1) is carried out at a temperature of 20°C to 40°C, and the reaction time is 20min to 120min; the hydrothermal recrystallization in step 1) is carried out at a temperature of 125°C to 175°C, and the reaction time is 12h to 24h.
8. The preparation method according to claim 5, characterized in that: Step 2) The electrochemical activation comprises the following operations: x Ni y -MOF nanofibers were loaded on a carbon electrode to make a working electrode, and then cyclic voltammetry scanning was performed with a Hg / HgO electrode as a reference electrode, a platinum electrode as a counter electrode, and a KOH solution as an electrolyte. The scanning rate was 1 mV / s to 100 mV / s, the scanning potential range was 0.925 V to 1.525 V, and the number of scanning circles was 5 to 200 circles.
9. An oxygen evolution reaction catalyst, characterized in that The invention comprises the metal hydroxide nanofibers according to any one of claims 1 to 4.
10. Use of the metal hydroxide nanofiber according to any one of claims 1 to 4 in producing hydrogen by electrolysis of water.